Monetary and exchange rate policies for the perfect storm: The case of the Bahamas, Barbados, Guyana, Haiti, Jamaica, Suriname, and Trinidad & Tobago - André Minella; Andrew Powell; Alessandro Rebucci; Nelson F. Souza-Sobrinho (Inter-American Development Bank, Research Department, 2009)
This study provides a set of tools to analyze the monetary and exchange rate policy issues in the seven countries of the Inter-American Development Bank's Caribbean region (The Bahamas, Barbados, Jamaica, Haiti, Guyana, Suriname, and Trinidad and Tobago). It then applies some of them to the analysis of the impact of the global turmoil on these economies in the last quarter of 2008. The paper also discusses, in light of both recent theoretical developments and key aspects of these economies, the monetary and exchange policy responses to the initial phase of the global turmoil.
Keywords: F33; E52; 330; Caribbean countries; Global crisis; Monetary policy